O criart, e suas relações com Tocantinópolis-TO - Damasceno, Eduardo Angelo de Oliveira (Universidade Federal do Tocantins, 2020)
The proposed work has as its main objective to deal with a handicraft association of Tocantinópolis -TO, known as CRIART, existing for 18 years and little known to the public. The association also serves various audiences, but only older women participate. From a better understandingof CRIART, the need arose to get in touch with the people who make up the association, to know what it is about, to investigate the reasons why people in the city do not know. To have contact with the history of the association, it was necessary to interview some of the artisans who produce their pieces in space, in order to better understand the context of the research. In the construction of the work, there was the need to talk about the culture in which association is inserted, because when talking about the non-recognition or non-visibility of the entity, the reason could be related to some aspect of the local culture. One of the main objectives to be achieved with the elaboration of this research is that CRIART is better recognized by the inhabitantsof the city. Thus, this research aims to promote the visibility of what is done by CRIART.